Hubungan Karakteristik Perawat dan Bidan dengan STIGMA pada Orang dengan HIV/AIDS (ODHA) di Puskesmas Talun Kabupaten Blitar - Sudarsono Sudarsono (Journal of Ners and Midwifery, 2015)
HIV/AIDS (Human Immunodeficiency Virus / Acquired Immune Deficiency Syndrome) has long been an issue along with the continued attention of various circles around the world, especially the health sector. The purpose of this study was to determine the characteristics of the relationship with the health workers in health centers stigma on people living with HIV Talun Blitar regency. This study used a cross-sectional study design with a population of 36 respondents that all the research sample. Collecting data using questionnaires. Analysis of data using statistical test Pearson and Spearman rho correlation with p ï‚£ 0.05. There is no relationship between education and stigma on people living with HIV, with a value of p = 0.367 in Spearman rho correlation test. There is a relationship between long working with the stigma on people living with HIV, with p = 0.046 in correlatioan Pearson test. There is a relationship between knowledge of HIV/AIDS stigma on people living with HIV, with p = 0.035 in correlatioan Pearson test. Need more attention from policy makers at government level for programs of prevention of transmission of HIV/AIDS among health workers, by providing a uniform and continuous training to all health workers.